2010
DOI: 10.1111/j.1464-0597.2009.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Justice and Citizenship Behaviors: A Study in the Portuguese Cultural Context

Abstract: Theoretical and empirical evidence suggests that justice and organisational citizenship behaviors (OCB), as well as the relationship between them, are not culture free. However, most studies have been carried out in parts of Asia and Northern Europe, and especially in the USA, shedding little understanding on the dynamics of justice and OCB in less-studied contexts. We show how four dimensions of organisational justice predict four dimensions of OCB in an under-studied context-Portugal, a feminine, collectivis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 63 publications
8
48
0
3
Order By: Relevance
“…High-quality treatment by a manager signals that a staff member has status and is held in high esteem in the workplace (Thau et al, 2013). Fair treatment is of particular significance according to the findings of various studies, which have confirmed that workplace treatment has far-reaching consequences for both employees and the organisation when it comes to the following: civility (Pearson, Andersson & Porath, 2005); job satisfaction (Hasan, 2010); organisational citizenship behaviours (Rego & Cunha, 2010); quality of work life (Moghimi, Kazemi & Samiie, 2012); turnover (Muzumdar, 2011); work behaviours (Le Roy, Bastounis & Minibas-Poussard, 2012); interpersonal and organisational deviance (Berry, Ones & Sackett, 2007); and workplace aggression (Hershcovis, Turner, Barling, Inness, LeBlanc, Arnold et al, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…High-quality treatment by a manager signals that a staff member has status and is held in high esteem in the workplace (Thau et al, 2013). Fair treatment is of particular significance according to the findings of various studies, which have confirmed that workplace treatment has far-reaching consequences for both employees and the organisation when it comes to the following: civility (Pearson, Andersson & Porath, 2005); job satisfaction (Hasan, 2010); organisational citizenship behaviours (Rego & Cunha, 2010); quality of work life (Moghimi, Kazemi & Samiie, 2012); turnover (Muzumdar, 2011); work behaviours (Le Roy, Bastounis & Minibas-Poussard, 2012); interpersonal and organisational deviance (Berry, Ones & Sackett, 2007); and workplace aggression (Hershcovis, Turner, Barling, Inness, LeBlanc, Arnold et al, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…Firm's size (as measured by the number of employees) was also included for control. The job was not solicited because, taking into account earlier research (Rego and Cunha, 2009c), the researchers conjecture that, in the cultural context of Portuguese organizations, characterized by high in-group collectivism and high power distance (Hofstede, 1991;Jesuino, 2002), asking ''too much'' personal information may generate a high number of nonresponses, reflecting fear of being identified.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Second, it is necessary to identify a variety of mediators between organizational justice and OCB to explain why organizational justice facilitates OCB (Rego and Cunha, 2010). Until now, a few mediators have been explored such as perceived organizational support (Moorman et al, 1998), trust (Konovsky and Pugh, 1994;Masterson et al, 2000), and leader-member exchange (Karriker and Williams, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a related issue of OI, even though some studies have considered the role of OI, previous studies have separately examined either the relationship between organizational justice and OI (De Cremer et al, 2006;Olkkonen and Lipponen, 2006;Rego and Cunha, 2010;Walumbwa et al, 2009) or between OI and OCB (Riketta, 2005;Van Dick et al, 2006). That is, there have been few attempts that explore the influence 531 Roles of OI and psychological contracts of organizational justice on OI as well as OCB by considering them simultaneously.…”
Section: Introductionmentioning
confidence: 99%